2003
DOI: 10.1677/joe.0.1760039
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism alters the expression of Bcl-2 family genes to induce enhanced apoptosis in the developing cerebellum

Abstract: Thyroid hormone (TH) deficiency results in delayed proliferation and migration of cerebellar granule cells. Although extensive cell loss during the development of the cerebellum under hypothyroid conditions is known, its nature and its mechanism are poorly understood. Bcl-2 family gene expression is known to determine the fate of cells to undergo apoptosis. We evaluated the effect of hypothyroidism on Bcl-2 family gene expression in the developing rat cerebellum. Electrophoresis and Western blotting were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 39 publications
5
48
1
2
Order By: Relevance
“…At the molecular level, we observed reduced expression of the proapoptotic gene Bad and increased expression of the antiapoptotic gene Bcl2 in vitro. This was in accordance with reduced Bcl2 expression in other CNS cell types due to hypothyroidism, such as cerebellar neurons (Muller et al, 1995;Singh et al, 2003), and shows the importance of thyroid hormone for cell survival in the brain.…”
Section: Discussionsupporting
confidence: 82%
“…At the molecular level, we observed reduced expression of the proapoptotic gene Bad and increased expression of the antiapoptotic gene Bcl2 in vitro. This was in accordance with reduced Bcl2 expression in other CNS cell types due to hypothyroidism, such as cerebellar neurons (Muller et al, 1995;Singh et al, 2003), and shows the importance of thyroid hormone for cell survival in the brain.…”
Section: Discussionsupporting
confidence: 82%
“…Here, we report that TH deficiency leads to structural alterations in mitochondria and enhanced translocation of apoptogenic proteins to cytosol, which results in the enhanced apoptosis during cerebellar neurogenesis observed previously (Xiao & Nikodem 1998, Singh et al 2003.…”
Section: Introductionmentioning
confidence: 68%
“…In euthyroid conditions, we found that Bax was predominantly localized in mitochondria during early developmental stages and decreased with age. Previously, we observed the high expression of Bcl-2 and Bcl-x L under euthyroid conditions (Singh et al 2003). It is reasonable to assume that Figure 5 Analysis of AIF translocation to cytosol.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This was documented initially in children with congenital hypothyroidism (Leneman et al, 2001;Hindmarsh, 2002;Hrytsiuk et al, 2002;Salerno et al, 2002;Rovet and Daneman, 2003). These findings were followed by animal studies mainly focused on cerebellar development, which occurs largely postnatally (Koibuchi and Chin, 2000;Thompson and Potter, 2000;Morte et al, 2002;Singh et al, 2003). Moreover, observations in humans (Cao et al, 1994;Haddow et al, 1999;Pop et al, 1999;Pop et al, 2003) provided important evidence that THs are also essential in early (fetal) brain development, and that the associated neurological deficits depend on the timing and severity of TH insufficiency.…”
Section: Nervous Systemmentioning
confidence: 97%